2021
DOI: 10.1002/elan.202100101
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Determination of NADH Using an Electrode Fabricated by Intercalation of Tetrabutylammonium Ions Into Graphite Electrode

Abstract: In this study, we present a strategy for the specific electrochemical detection of NADH in human blood serums using modified electrode fabricated by intercalation of tetrabutylammonium ions (TBA+) into pencil graphite electrode (TBA+/PGE). In order to implement this protocol, a modification process in the potential range (−0.2) to (−2.75) V was performed in DMSO containing 0.1 M TBAP by CV method. The characterization processes of the prepared sensor were carried out using CV, EIS, FT‐IR, XPS, and SEM methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…There have been a great number of studies reported about designing sensors to determine NADH, due to its significant role as a major contributor to the electron transfer reactions in living cells and participant in most other enzyme reactions [54,55]. The oxidation behavior of NADH and folic acid is depended on the pH value of the solution.…”
Section: Electrochemical Investigationmentioning
confidence: 99%
“…There have been a great number of studies reported about designing sensors to determine NADH, due to its significant role as a major contributor to the electron transfer reactions in living cells and participant in most other enzyme reactions [54,55]. The oxidation behavior of NADH and folic acid is depended on the pH value of the solution.…”
Section: Electrochemical Investigationmentioning
confidence: 99%
“…26,27 On the other hand, when the S2p spectrum was examined, these peaks were observed at 165.0, 168.88, and 170.05 eV indicating the presence of C–S–C and C–SO x –C– ( x : 2, 3) sub-bindings, respectively. 28–30 In light of all this information, it can be concluded that S-GO powders were successfully synthesized in the synthesis.…”
Section: Resultsmentioning
confidence: 92%
“…Quantitative analyses of NADH in diverse samples can be performed using different instrumental techniques namely colourimetry/ spectrophotometry [7][8][9], spectrophotofluorometry [10][11][12], capillary electrophoresis [13,14], reversed phase-high pressure liquid chromatography (RP-HPLC) with ultraviolet (UV) [15], mass spectrometry (MS) [16], and MS/MS [17] detectors, ion-chromatography-MS (IC-MS) [18], amperometry [19][20][21][22][23][24], voltammetry [3,25,26], and electrochemiluminescence (ECL) [27][28][29][30] combined with flow injection (FI) technique and/or batch methods and conductance ratiometry [31]. Although, a few of these methodologies offer good sensitivity and precision, but need lengthy procedures, considerable amounts of solvents, complex equipment, multiple steps of sample preprocessing and long investigation times.…”
mentioning
confidence: 99%